(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
The goal is to propose preventive methods based on identifying the characteristics of the tuberculosis-related epidemiological process in medical personnel performing autopsies of bodies with active tuberculosis. Today, tuberculosis infection is characterized by multiple drug resistance, which complicates the treatment aspects of patients and creates tension for infecting others. The situation regarding the incidence of tuberculosis among medical workers working as proctors in Surgut city for the period from 2011 to 2018 was studied. A high level of tuberculosis morbidity among medical workers - pathologists and forensic medical examination physicians - is shown, which requires appropriate anti-epidemic measures among specialists of these categories.